TECHNOLOGY IN BUSINESS EDUCATION (LEARNING APPLICATIONS - ASSIGNMENT SUBMISSIONS IN YOUTUBE) - Umachandran, Krishnan (PEOPLE: International Journal of Social Sciences, 2018)
Professional internships presented during academic learning levels consume prudently edited classifications of screen capture, collected as a favorite or dedicated display in a student’s communication about the firm’s operations and existence in the society. Academic assignments are stipulated for curriculum clearance, marks percentage or the course grade. As the submission is purely pro-business and a win-win for the student to become a potential employee in the future, the samples presented were not given ample critical attention. YouTube is a way to sensationalize the standing to the viewers through computer-mediated message, hence the assignment methodology to be interesting for application, feasibility check, adequate workload for clearing the learning objectives and easy to cut corners without sacrificing educational quality was applied. The enrichment in learning stimulated the learning reasonableness among students, and reduced the evaluation burden in teacher without compromising learning goals. Therefore, to achieve the success in online submission of assignments by students, certain parameters such as the time frame, calendar plan and execution of an assignment were effectively managed.